2004
DOI: 10.1128/jb.186.9.2586-2593.2004
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Active Role of a Novel Nuclease from Helicobacter pylori in the Horizontal Transfer of Genetic Information

Abstract: Helicobacter pylori is a gram-negative bacterium that colonizes the human stomach, causes gastritis, and is associated with ulcers and gastric cancer. H. pylori is naturally competent for transformation. Natural genetic transformation is believed to be essential for the genetic plasticity observed in this species. While the relevance of horizontal gene transfer in H. pylori adaptiveness and antibiotic resistance is well documented, the DNA transformation machinery components are barely known. No enzymatic acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 41 publications
3
23
1
Order By: Relevance
“…It was also shown that NucT is not simply secreted but instead appears to be associated with the bacterial outer membrane (39). This seems to indicate that the bacterium requires the protein to be within close proximity of its membrane, possibly to avoid the nuclease from being removed (as a secreted protein is) by the turnover of gastric mucus into the gut.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…It was also shown that NucT is not simply secreted but instead appears to be associated with the bacterial outer membrane (39). This seems to indicate that the bacterium requires the protein to be within close proximity of its membrane, possibly to avoid the nuclease from being removed (as a secreted protein is) by the turnover of gastric mucus into the gut.…”
Section: Discussionmentioning
confidence: 98%
“…H. pylori has long been known to possess robust external nuclease activity, similar to numerous campylobacters (38), but this ability to degrade DNA has been examined only with regard to natural transformation (39,40) and never in the context of purine salvage and metabolism. As the uptake of DNA by the ComB system appeared to play no role in purine utilization in metabolism, we next tested the possibility that external DNases were digesting external DNA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations